Evaluation of Macrocytic Anemia in a tertiary care hospital in Kanchipuram, Tamil Nadu, India (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Macrocytosis is used to describe large erythrocytes with a Mean Corpuscular Volume(MCV) of >101fl. There are a numberof causes with characteristic haematological, biochemical and bone marrow findings which lead to macrocytic anemia.Materials and Methods: We conducted an observational study of 62 cases in the Hematology Laboratory, at a tertiary care hospital inKanchipuram with the aim to identify and evaluate macrocytic anemia and the underlying causes in routine hemograms and peripheral bloodsmears and correlate with the accompanying haematological features along with biochemical and bone marrow studies done in selectedcases.Results: Out of 62 cases received during the study period, Alcoholic Liver Disease emerged as the most common underlying cause (21cases), followed by Hypothyroidism (16 cases) , Non-Alcoholic Liver Disease (11 cases), Vitamin B12 deficiency (9 cases) and drugrelated causes (5 cases). Macrocytes were overall the most common peripheral blood smear finding accompanied by macro-ovalocytes andhypersegmented neutrophils in cases of Vitamin B12 deficiency.Conclusions: Macrocytic anemia is commonly seen in alcoholic as well as several non-alcoholic cases, which should be fairly evaluated forfurther treatment and prevention.